Verbalization of the online social processes in the modern english language - Kalashnykova, M.Yu.; Калашникова, Марина Юріївна (Warsaw, 2020)
The development of social network services became one of the reasons for a new reality formation, which is called virtual reality – VR. The present research is concentrated on the study of the active neology processes based on the online social activity verbalization that are detected in the modern English language. This phenomenon is the evidence of the language supersystem reaction to the out-of-the-ordinary changes that take place in all fields of human activity caused by the new technologies. The article is concentrated on how the new ways and methods of new lexemes formation make the way to refinement on the basis of the study and analysis of the vocabulary proliferation. Important processes of self-regulation and self-organization of the language system are energized with the help of external stimulators that are of value for the modern studies of the English language.
Keywords: concept; neologism; culture; society; virtual reality